Research of distribution network terminal communication security architecture based on cryptographic algorithm - LI Lu; XIE Yinghong; LI Weifan; DING Kai; LI Feng (Zhejiang dianli, 2022)
The security requirements of a terminal communication system for distribution automation are studied. Moreover， a communication security architecture for distribution automation terminal conforming to the actual situations of China is designed to solve the security problem in distribution automation terminal communication in an open interconnection environment. The security architecture is based on cryptographic algorithm standards. The protocol is modified and designed without affecting communication efficiency. The double encryption and authentication functions of the application layer and the network layer are realized and applied to the communication of the distribution network terminal. The analysis of the RFC （request for comments） standard and cryptographic algorithm standard， security analysis， scheme comparison， and test verification confirm that the communication architecture is eligible for encryption and authentication capabilities. Besides， it can overcome the vulnerability of the terminal protocols and reduce the algorithm's complexity while improving communication efficiency.